Efficacy of Preoperative Enhanced Recovery Protocols Versus Standard Care in Urologic Surgery - Kakar, Muhammad Musa; Asadullah; Asadullah; Nawaz, Ali; Kakar, Sana Ullah (Indus Journal of Bioscience Research, 2025)
Background: A contemporary, multimodal perioperative strategy, enhanced recovery after surgery (ERAS) procedures are designed to reduce surgical stress, preserve physiological function, and speed up recovery in order to improve patient outcomes. ERAS principles were first applied in colorectal surgery, but they have since been modified for use in urology and other surgical specialties. The preoperative effectiveness of ERAS in comparison to conventional standard treatment in major urologic procedures is still not well understood in local clinical settings, despite mounting evidence of its advantages. Objective: This study aimed to evaluate the efficacy of preoperative ERAS protocols versus standard perioperative care in major urologic surgeries—specifically radical cystectomy and radical prostatectomy—by comparing clinical outcomes, patient satisfaction, and healthcare professionals’ perspectives. Methods: A tertiary care hospital in Quetta, Pakistan, was the site of a qualitative comparative study. Using purposive sampling, a total of 100 participants—70 patients and 30 medical professionals—were chosen. Using a pre-made guide, semi-structured interviews were performed to examine preoperative preparation, recovery, pain management, and satisfaction-related experiences and perceptions. Prior to inclusion, all subjects provided written informed permission, and the hospital’s Institutional Review Board granted ethical approval. Results: Compared to patients receiving normal treatment, those treated using ERAS procedures showed improved recovery profiles. The ERAS group was mobilized earlier (82.9% vs. 45.7%), had fewer surgical problems (14.3% vs. 37.1%), shorter mean hospital stays (5.2 vs. 8.7 days), and resumed oral intake more quickly (77.1% vs. 40.0%). In terms of psychological comfort, pain control, and preoperative counseling, patient satisfaction was significantly higher in the ERAS group. Improved interdisciplinary collaboration and less postoperative stress were recognized by medical professionals, but they also pointed to issues with institutional implementation support and inadequate training. Conclusion: When it comes to improving recovery and clinical outcomes for patients undergoing major urologic procedures, preoperative ERAS treatments outperform traditional standard care. ERAS encourages a quicker recovery, fewer problems, and greater satisfaction by combining patient education, early postoperative rehabilitation, and optimal preoperative treatment. In order to guarantee consistent application, the study suggests that ERAS routes be adopted more widely in urologic surgery through organized institutional support and ongoing staff training.